Transformational Leadership on Employee Engagement: The Work Motivation as a Moderation Variable - yulman, thio; Trinanda, Okki (Universitas Negeri Padang, 2023)
This study aims to prove the effect of Transformational Leadership on Employee Engagement, besides that this research also proves the impact of Work Motivation in strengthening the relationship between Transformational Leadership and Employee Engagement. The research was conducted on employees of the Tanah Datar District Communication and Informatics Office. The process of collecting data and information was carried out by means of a survey, namely distributing questionnaires to employees within the Communication and Informatics Office of Tanah Datar Regency. This research is a causative research. The data analysis technique used is Structral Equation Modeling (SEM). The stages of data processing are assisted by using the SmartPLS4.0 application. The results of the study show that: (1) Transformational leadership has a positive and significant impact on Employee Engagement. (2) Work motivation has a positive and significant effect on Employees Engagement. (3) Transformational leadership has a positive and significant effect on Work Motivation (4) Work Motivation strengthens the relationship between Transformational Leadership and Employee Engagement at the Communication and Informatics Office of Tanah Datar Regency